Financial Institutions of the Social Economy as a Tool for Rural Development. Involvement of Endogenous Resources - Ruiz Guerra, Ignacio (Cooperativismo & Desarrollo, 2013)
Over the years it has been demonstrated that despite the cycles of boom, crises or stagnation, the social economy sector subsists in the best situations and grows in the worst. The reason is clear: belonging to a place, a land and a society. This is consistent with the banking as social economy is an economic boost in rural areas and is responsible for the modernization and technical improvement in the local. From a reflective process regarding research findings in Spanish credit unions, with the support of Fundación Caja Rural de Toledo, the Universidad de Castilla-La Mancha and more recently with the Universidad Complutense de Madrid, it is concluded that in every impact assessment process of the actions of the social economy is essential to consider what elements are responsible for the valorization of their own resources and elementary for the creation of stable job in rural areas. The logic of the social economy is an important factor in maintaining subsistence economic structures, but also generates competitive dynamics based on the value added to its activity, its responsibility to society and rural development.
Keywords: rural development; dynamics; social economy; valorization